Leading academic change : - Lucas, Ann F. (Jossey-Bass, 2000)
For the 80,000 department chairs working on campuses across the nation, this visionary yet practical book shows how to manage academic change at the department level. It provides useful ideas and strategies on handling resistance to change, transforming departments into productive learning communities, and improving educational quality for students. In twelve incisive chapters, top academic scholars, authors, and consultants address topics and trAnds as diverse as service learning, technological change, curriculum renewal, faculty reward systems, and post-tenure review. They offer effective models to help department chairs and administrators work through the change process, including recommAndations based on real-world experiences. They also integrate the latest research with examples of best practices into a readable, accessible format. Whether you are a department chair, administrator, or a faculty member aspiring to improve your department, Leading Academic Change is the expert's guide to mobilizing faculty energy towards academic success.